Association of serum interleukin-6 and C-reactive protein with depressive and adjustment disorders in COVID-19 inpatients - Maria Iglesias-González; Marc Boigues; David Sanagustin; Maria Giralt-López; Jorge Cuevas-Esteban; Eva Martínez-Cáceres; Crisanto Díez-Quevedo (Brain, Behavior, & Immunity - Health, 2022)
Background: Immune mechanisms are part of the pathophysiology of mental disorders, although their role remains controversial. In depressive disorders a chronic low-grade inflammatory process is observed, with higher interleukin-6 (IL-6) values. Furthermore, in SARS-CoV2 infection, which is closely related to depressive disorders, there is a proinflammatory cascade of cytokines that causes systemic inflammation. Methods: The present study evaluates the relationship between IL-6 and C-reactive protein (CRP) serum levels and the presence of depressive and adjustment disorders in a sample of 1851 patients admitted to hospital for SARS-CoV2 infection from March to November 2020. Concentrations of IL-6 and CRP were determined within the first 72 ​h at admission and compared among groups of patients according to previous history and current presence of depression or adjustment disorders. Results: IL-6 serum levels were significantly higher in the group of patients with depression and adjustment disorders compared to patients without such disorders (114.25 ​pg/mL (SD, 225.44) vs. 86.41 (SD, 202.97)), even after adjusting for several confounders. Similar results were obtained for CRP (103.94 ​mg/L (SD, 91.16) vs. 90.14 (SD, 85.73)). The absolute levels of IL-6 and CRP were higher than those of previous depression studies, and differences were only found for the subgroup of De Novo depressive or adjustment disorders. Conclusions: Serum concentrations of IL-6 and CRP are higher in COVID-19 patients with De Novo but not persistent depressive or adjustment disorders. Clinical features such as fatigue, asthenia, anhedonia, or anxiety can be the basis for this finding.